The Effects of Exercise on Plaque Volume and Composition in a Mouse Model of Early and Late Life Atherosclerosis - Stanton, Kelly M.; Liu, Hongjuan; Kienzle, Vivian; Bursill, Christina; Bao, Shisan; Celermajer, David S. (Frontiers in Cardiovascular Medicine, 2022)
Background Exercise is associated with a less atherogenic lipid profile; however, there is limited research on the effect of exercise on atherosclerotic plaque composition and markers of plaque stability. Methods A total of 110 apolipoprotein (apo)E−/− mice were placed on a chow diet and randomly assigned to control or exercise for a period of 10 weeks, commencing either at 12 weeks of age (the early-stage atherosclerosis, EA group) or at 40 weeks of age (the late-stage atherosclerosis, LA group). At the end of the exercise period, blood was assayed for lipids. Histologic analysis of the aortic sinus was undertaken to assess plaque size and composition that includes macrophage content, monocyte chemoattractant protein (MCP)-1, matrix metalloproteinase-2 (MMP-2), and tissue inhibitors of metalloproteinase 1 and 2 (TIMP-1 and 2). Results A total of 103 mice (38 EA, 65 LA) completed the protocol. In the EA group, exercise reduced plasma total cholesterol (TC) (−16%), free cholesterol (−13%), triglyceride (TG) (−35%), and phospholipid (−27%) levels, when compared to sedentary control mice (p < 0.01). In the EA group, exercise also significantly reduced plaque stenosis (−25%, p < 0.01), and there were higher levels of elastin (3-fold increase, p < 0.0001) and collagen (11-fold increase, p < 0.0001) in plaques, compared to control mice. There was an increase in plaque MMP-2 content in the exercise group (13% increase, p < 0.05) but no significant difference in macrophage or MCP-1 content. In the LA group, exercise reduced plaque stenosis (−18%, p < 0.05), but there was no significant difference in plaque composition. There was no difference in macrophage, MCP-1, or MMP-2 content in the LA groups. TIMP-1 was lower with exercise in both the EA and LA groups (−59%, p < 0.01 and −51%, p < 0.01 respectively); however, there was no difference in TIMP-2 levels. Conclusion A 10-week exercise period reduces atherosclerotic plaque stenosis when commenced at both early- and late-stage atherosclerosis. Intervening earlier with exercise had a greater beneficial effect on lipids and plaque composition than when starting exercise at a later disease stage.